2014
DOI: 10.1111/vru.12234
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Pulmonary Vasculature on Thoracic Radiographs in Healthy Dogs Compared to Dogs With Mitral Regurgitation

Abstract: This study reassessed the previously reported radiographic method of comparing pulmonary vessels versus rib diameter for differentiating healthy dogs and dogs with mitral regurgitation. The width of the right cranial pulmonary artery and vein at the fourth rib level, right caudal pulmonary artery and vein at the ninth rib level, and the diameters of the fourth rib and ninth rib were measured in prospectively recruited healthy dogs (n = 40) and retrospectively recruited dogs with mitral regurgitation (n = 58). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
1
7
1
Order By: Relevance
“…This is the first study with brachycephalic dogs that used CT to measure bronchial collapsibility at forced expiration and compare the bronchial collapsibility quantitatively for each pulmonary lobe. The measurement of bronchial collapsibility at forced expiration is considered important in brachycephalic dogs as upper respiratory disorders are common in these animals and bronchial collapse can cause elevation of pulmonary pressure and contribute to pulmonary hypertension in these breeds …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study with brachycephalic dogs that used CT to measure bronchial collapsibility at forced expiration and compare the bronchial collapsibility quantitatively for each pulmonary lobe. The measurement of bronchial collapsibility at forced expiration is considered important in brachycephalic dogs as upper respiratory disorders are common in these animals and bronchial collapse can cause elevation of pulmonary pressure and contribute to pulmonary hypertension in these breeds …”
Section: Discussionmentioning
confidence: 99%
“…and conducted using commercially available statistics software (SPSS Statis- In comparisons between the collapsibility determined by cross sectional CT images versus CT MPR images and cross-sectional CT images versus radiographs, the collapsibility of the right caudal lobar bronchi determined by CT MPR images and radiographs was significantly greater than that in cross sectional CT images in all respiratory are common in these animals and bronchial collapse can cause elevation of pulmonary pressure and contribute to pulmonary hypertension in these breeds. 23 Various studies have focused on bronchial abnormalities in brachycephalic dogs. 4,17,24,25 However, none of these studies have evaluated the bronchial collapsibility of brachycephalic dogs at forced expiration using CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Only the diameters of bronchi for the right cranial lobe and right caudal lobe were visually inspected because the other bronchi were frequently superimposed on one another on the radiographs and could not be finely visualized. The following were measured on thoracic radiographs and dorsal and sagittal CT multiplanar reconstruction images: (1) The distance between the right cranial pulmonary artery and vein at the level of the fourth rib on the left lateral radiographic image and the sagittal CT multiplanar reconstruction images; (2) the distance between the right caudal pulmonary artery and vein at the level of the ninth rib on the dorsoventral radiographic image and dorsal CT multiplanar reconstruction images (Figure ) . It should be noted that the distance between the pulmonary artery and vein is an approximation of the diameter of the bronchus on radiographs .…”
Section: Methodsmentioning
confidence: 99%
“…A recent publication reported that the mean CrPV/CrPA and CdPV/CdPA in dogs without cardiac disease (controls) were 0.99±0.6 and 1.04±0.19, respectively, as the focus of the study was venous congestion. 28 Our study measured arterial-to-venous ratios as pulmonary artery dilation is the main vascular radiological pattern of PH. An additional discrepancy between this paper and ours was that our CdPA/CdPV measurements were made at the level of the ninth as opposed to the eleventh intercostal space.…”
Section: Discussionmentioning
confidence: 99%